In Vitro Antioxidant Activities and the Therapeutic Potential of Some Newly Synthesized Chalcones Against 4-Acetaminophenol Induced Hepatotoxicity in Rats. Issue 1 (12th March 2021) - Akhtar, Muhammad Shoaib; Rehman, Aziz-Ur-; Arshad, Haroon; Malik, Abdul; Fatima, Muheer; Tabassum, Tahira; Raza, Abdul Rauf; Bukhsh, Munnaza; Murtaza, Mian Anjum; Mehmood, Malik Hassan; Sultan, Ayesha; Rasool, Ghulam; et al.
The lack of safety and efficacy of existing hepatoprotective agents urge the need to explore novel hepatoprotective agents. The research work was planned to study the therapeutic potential of some newly synthesized chalcones against 4-acetaminophenol induced hepatotoxicity in rats. Male albino rats (N = 30) were divided into 6 groups of 5 animals each i.e. group I; Toxic control (4-acetaminophenol), group II; normal control (Normal saline), group III; Positive control (silymarin; 50 mg/kg bw) and groups IV-VI (test groups) treated with 3 chalcone analogues i-e 3a, 3f & 3 g (100, 150, 150 mg/kg bw, respectively). All the study group animals were administered with 4-acetaminophenol to induce hepatotoxicity except normal control. Following hepatotoxicity induction, test group animals were administered with selected doses of test compounds and toxic group animals left untreated. Liver enzymes including ALT, AST, ALP and serum bilirubin were determined photometrically. Antioxidant activities of test compounds were also determined. Histopathological examination of liver biopsies was also carried out through H & E staining. The test chalcones (3a, 3f &3 g ) significantly decreased the levels of liver enzymes and serum bilirubin toward normal and the pattern of results in the test group animals were comparable to silymarin administered animals indicating the hepatoprotective potential of test compounds. Moreover, the test chalcones (3a, 3f &3 g ) antagonized the effect of 4-acetaminophenol and thus, raised the catalase (CAT) and superoxide dismutase (SOD) while decreased the malondialdehyde (MDA) in experimental animals. The test chalcones (3a, 3f &3 g ) on histological examination of liver showed improvement of tissue morphology. The study concluded that the tested compounds have antioxidant potential and may act as hepatoprotective agent. However, in-depth studies are required to validate their safety and to elucidate the exact mechanism of action.